THE EFFECT OF SPECIAL REHABILITATION EXERCISES ACCORDING TO A PROPOSED PROGRAM TO TREAT LUMBAR DEFORMITY AND LOWER BACK PAIN - Assistant prof. Suhad Ibrahim Hamdan (Proximus Journal Publishing, 2025)
The ages of 13-15 years are exposed to the problem of postural deformity in schools, and the most common of these deformities is the deformity of the lumbar cavity due to the irregularity in practicing school sports, and the other matter is how to carry school bags loaded with school materials incorrectly and walking long distances, all of these factors combined may be a cause of postural deformities and the spread of lumbar cavity deformity among students, so we recommend that attention should be paid to physical education classes and educating students and parents to practice sports because of its great importance in maintaining the safety of the body from postural deformities, as this helps to achieve a happy life without feeling pain or facing injury or postural deformity. From here, the research problem and its importance were determined in the effect of special rehabilitation exercises according to a proposed program to treat lumbar cavity deformity and lower back pain for ages (13-15) years.
Keywords: Specific exercises; suggested training program; lumbar disc deformity